2010
DOI: 10.1111/j.1365-3032.2010.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of host‐plant chemical stimuli for the European grape berry mothEupoecilia ambiguella

Abstract: Abstract. Olfaction is of major importance for survival and reproduction in moths. Males possess highly specific and sensitive olfactory receptor neurones to detect female sex pheromones. However, the capacity of male moths to respond to host-plant volatiles is relatively neglected and the role that such responses could play in the sensory ecology of moths is still not fully understood. The present study aims to identify host-plant stimuli for the European grape berry moth Eupoecilia ambiguella Hb. (Tortricida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Wound-induced (Z)-3-hexen-1-ol has been shown to be an important infochemical for herbivore repellence/attraction and natural enemy attraction in tritrophic interactions, as well as for induction of gene expression in neighboring unattacked plants; therefore, this compound could be used to develop novel insect pest control strategies (Wei & Kang, 2011). Electrophysiological studies have revealed that numerous herbivores (lepidopterans, hemipterans, dipterans, coleopterans, and a hymenopteran) exhibited EAG responses to (Z)-3-hexen-1-ol (Suckling et al, 2001;Ansebo et al, 2004;Byers et al, 2004;Bruce et al, 2005;Germinara et al, 2009;Liu et al, 2009;Williams et al, 2010;Schmidt-B€ usser et al, 2011). Many phytophagous insects have been shown to be attracted by (Z)-3-hexen-1ol in field trap and/or laboratory wind tunnel studies with, for example, Phyllopertha horticola (L.) (Ruther & Tolasch, 2004), female Cephus cinctus Norton (Piesik et al, 2008), and male Cydia pomonella L. and Spodoptera exigua EAG response (mV) Concentration (mol l -1 ) Concentration (mol l -1 ) Figure 3 Mean (AE SE) EAG responses (mV) of male and female Cryptorrhynchus lapathi to a range of concentrations (1-10 À5 mol l À1 ) of six selected volatiles.…”
Section: Discussionmentioning
confidence: 99%
“…Wound-induced (Z)-3-hexen-1-ol has been shown to be an important infochemical for herbivore repellence/attraction and natural enemy attraction in tritrophic interactions, as well as for induction of gene expression in neighboring unattacked plants; therefore, this compound could be used to develop novel insect pest control strategies (Wei & Kang, 2011). Electrophysiological studies have revealed that numerous herbivores (lepidopterans, hemipterans, dipterans, coleopterans, and a hymenopteran) exhibited EAG responses to (Z)-3-hexen-1-ol (Suckling et al, 2001;Ansebo et al, 2004;Byers et al, 2004;Bruce et al, 2005;Germinara et al, 2009;Liu et al, 2009;Williams et al, 2010;Schmidt-B€ usser et al, 2011). Many phytophagous insects have been shown to be attracted by (Z)-3-hexen-1ol in field trap and/or laboratory wind tunnel studies with, for example, Phyllopertha horticola (L.) (Ruther & Tolasch, 2004), female Cephus cinctus Norton (Piesik et al, 2008), and male Cydia pomonella L. and Spodoptera exigua EAG response (mV) Concentration (mol l -1 ) Concentration (mol l -1 ) Figure 3 Mean (AE SE) EAG responses (mV) of male and female Cryptorrhynchus lapathi to a range of concentrations (1-10 À5 mol l À1 ) of six selected volatiles.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a behavioral response is frequently elicited by compound blends, where single compounds can often be exchanged with no apparent loss of activity Tasin et al, 2006Tasin et al, , 2010Pinero et al, 2008;Riffell et al, 2009;Cha et al, 2011;Schmidt-Busser et al, 2011;Thoming and Knudsen, 2014). This makes it particularly difficult to determine which plant volatiles encode host finding in phytophagous insects.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of the texture B, green colour and a spherical surface (plane on the bottom side and convex on the top side) provides the basic concept for the creation of an artificial egg‐laying site. In order to enable a competitiveness of the artificial surface to grapes, it is also important to analyse the impact of volatiles emitted by the host plant, which attract females in long and short range (Anfora et al., ; Schmitt‐Büsser, von Arx, Connetable, & Guerin, ; Tasin et al., , ), and the role of wax layers of the grape surface, which may also impact the oviposition decision of female berry moths (Maher & Thiéry, 2004b; Maher et al., ). These results should be also considered in the development of an artificial oviposition‐monitoring tool, which actually reflects the pest infestation.…”
Section: Discussionmentioning
confidence: 99%